Charm city - Lippman, Laura, 1959- (Lippman, Laura, 1959- Tess Monaghan mystery., 2007)
When a lurid exposé mysteriously appears on the front page of the Baltimore Beacon-Light and causes a business tycoon to commit suicide in his garage, private investigator Tess Monaghan takes on the case.